Reducing the electrogram review burden imposed by insertable cardiac monitors. (9th February 2022) - Gardner, Roy S.; Quartieri, Fabio; Betts, Tim R.; Afzal, Muhammad R.; Manyam, Harish; Badie, Nima; Dawoud, Fady; Sabet, Leyla; Davis, Kevin; Qu, Fujian; Ryu, Kyungmoo; Ip, John
Abstract: Background: Insertable cardiac monitors (ICMs) are essential for ambulatory arrhythmia diagnosis. However, definitive diagnoses still require time‐consuming, manual adjudication of electrograms (EGMs). Objective: To evaluate the clinical impact of selecting only key EGMs for review. Methods: Retrospective analyses of randomly selected Abbott Confirm Rx™ devices with ≥90 days of remote transmission history were performed, with each EGM adjudicated as true or false positive (TP, FP). For each device, up to 3 "key EGMs" per arrhythmia type per day were prioritized for review based on ventricular rate and episode duration. The reduction in EGMs and TP days (patient‐days with at least one TP EGM), and any diagnostic delay (from the first TP), were calculated versus reviewing all EGMs. Results: In 1000 ICMs over a median duration of 8.1 months, at least one atrial fibrillation (AF), tachycardia, bradycardia, or pause EGM was transmitted by 424, 343, 190, and 325 devices, respectively, with a total of 95 716 EGMs. Approximately 90% of episodes were contributed by 25% of patients. Key EGM selection reduced EGM review burden by 43%, 66%, 77%, and 50% (55% overall), while reducing TP days by 0.8%, 2.1%, 0.2%, and 0.0%, respectively. Despite reviewing fewer EGMs, 99% of devices with a TP EGM were ultimately diagnosed on the same day versus reviewing all EGMs. Conclusion: Key EGM selection reduced the EGM review substantially with no delay‐to‐diagnosis in 99% of patients exhibiting true arrhythmias. Implementing these rules in the Abbott patient care network may accelerate clinical workflow without compromising diagnostic timelines.